An Analysis of Sisingaan Performance in Subang From Language Perspective - Septy Indrianty; Sansan Yuliansah (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2023)
Sisingaan performances are one manifestation of the results of cultural societies in which there is an auditive, visual, and text message. The research carried out semantic-semiotic and etnopedagogy studies on sisingaan performances in Subang Regency from a language perspective. The method used is descriptive qualitative and in dissecting this research the approaches were semantics, semiotics and ethnopedaogy. In language research, the sisingaan is known to experience a shift in meaning based on its function and existence. Sisingaan characterization is interpreted as a form of resistance to colonialism. The result showed that the denotation of Sisingaan itself was made from wood, yarn and so on. Then, the connotation stage sisingaan art evolves its meaning into something that is historically principle and very rich in philosophy. Sisingaan is interpreted as one of the ways to convey criticism and resistance to the invaders, this is indicated by the many writings in the media which regularly write that sisingaan is a symbol of resistance to invaders (Dutch and British). Society symbolizes sisingaan structure as symbols that have meaning, four people who guide sisingaan are symbolized as oppressed people, who are forced to submit to invaders, then sisingaan is symbolized as occupying power over the occupied territories, in this matter is the Subang district. Furthermore, the child who occupies the lion is symbolized as the young generation of the nation who will continue the resistance against the invaders and is predicted to become the leader of the nation.